A kinematic analysis of a judo leg sweep: Major outer leg reap - Osoto-gari - Imamura, R.; Johnson, B. (Sports Biomechanics, 2003)
Twenty male judo players (10 black belt; 10 novice) executed tha major outer leg reap, osoto-gari, with maximal effort. Each throw was recorded within the two-dimensional sagittal plane using a 60 Hz video camera. Kinematic data that best described the power of the 'tori's' (thrower's) sweeping leg and the velocity of the 'uke's' (recipient's) falling body were analysed using a Peak Performance Utilities Inc. Motus system. Data from black belt and novice groups were statistically analysed using a one-way MANOVA (p=.05). Statistical analysis found only two variables for the 'tori' (peak angular velocity of the trunk; TTRK, and peak angular velocity of the ankle; TANK) to be significantly different. Large TTRK values for the black belt group indicated a proficient ability to create large momentum on the upper body of the 'uke'. Significantly larger differences in trunk rotation velocities of the 'uke' by the black belt group reinforced this notion. These differences were attributed to good upper body to upper body contact or impact, which is considered an important aspect of the 'osoto-gari'. Significant differences in TANK values stressed the importance of executing plantar flexion near sweep contact. The results emphasised the importance of using the sweeping leg in a sequential kinetic link motion rather than as a single rigid segment.